👤

1/ (y+3)²+(y-3)²=
2/ 53²+47² =
3/ (5x+2)²+1+3x)² =

Pouvez vous m'aidez s'il vous plait ??


Répondre :

Bonjour

(y+3)² + (y-3)²
= (y² + 2*y*3 + 3²) + (y² - 2*y*3 + 3²)
= y² + 6y + 9 + y² - 6y + 9
= 2y² + 18

53² + 47²
= 2 809 + 2 209
= 5 018

(5x+2)² + (1+3x)²
= [(5x)² + 2*5x*2 + 2²] + [1² + 2*1*3x + (3x)²]
= 25x² + 20x + 4 + 1 + 6x + 9x²
= 34x² + 26x + 5

Voilà j'espère avoir pu t'aider ^^
Bonjour

A= (y+3)² + (y-3)²
A= (y² + 2×y×3 + 3²) + (y² - 2×y×3 + 3²)
A= y² + 6y + 9 + y² - 6y + 9
A= y² + y² + 6y - 6y + 9 + 9
A= 2y² + 18

B= 53² + 47²
B= 2 809 + 2 209
B= 5 018

C= (5x+2)² + (1+3x)²
C= [(5x)² + 2×5x×2 + 2²] + [1² + 2×1×3x + (3x)²]
C= 25x² + 20x + 4 + 1 + 6x + 9x²
C= 25x² + 9x² +20x + 6x +4 +1
C= 34x² + 26x + 5

Ps : apprend t'es identités remarquables :
(a+b)²= a² + 2ab + b²
(a-b)²= a² - 2ab + b²

Voilà ^^